Sistem Layanan Pelanggan Menggunakan BOT WHATSAPP Pada Usaha Kaos Sablon - Nugroho, Soma Setiawan Ponco; Miharja, Muhammad Najamuddin Dwi; Ridwan, Achmad; Suprapto, Suprapto; Soma Setiawan Ponco Nugroho (Jurnal Pelita Teknologi, 2023)
Screen printing t-shirt business on a large scale level can be included as a manufacturing business. In the screen printing t-shirt business, business actors often focus more on t-shirt production and printing designs, so that the container for customer information is often overlooked. With more and more customers in the screen printing t-shirt business, businesses often take up their time in serving and providing information to customers. The media that customers usually use in asking for information is usually via WhatsApp. The implementation of customer service using whatsapp bots in screen printing t-shirt businesses is expected to be a solution so that good relations are maintained between customers and businesses.